FACTORS AFFECTING STUDENT FINANCIAL BEHAVIOR IN DIGITAL TRENDS - Sheda, Ghegana Ariel; Muharrami, Rais Sani (I-Finance Journal, 2023)
This study discusses the influence of Islamic financial literacy, locus of control and religiosity on student financial management in the digital era. The respondents in this study were Febi students of Raden Mas Said State Islamic University Surakarta with a total of 177 respondents. The data collection process is carried out by disseminating questions and answers using primary quantitative methods through questionnaires. This study used multiple linear regression analysis method. This study concluded that there is a positive and significant influence between sharia financial literacy on financial management, there is a positive and significant influence between locus of control on financial management and no influence on religiosity on student financial management. Based on the results of the research conducted, the R Square value was obtained at 0.244 or 24.4%. While the remaining 75.6% was influenced by other variables that were not examined in this study. These findings can certainly be part of the reference for students in financial management in the digital era. The conclusion is that Islamic financial literacy and locus of control can influence student financial management in the digital era. Meanwhile, religiosity cannot influence student financial management in the digital era.